2001
DOI: 10.1037/0021-9010.86.2.326
|View full text |Cite
|
Sign up to set email alerts
|

Voice and cooperative behavior as contrasting forms of contextual performance: Evidence of differential relationships with Big Five personality characteristics and cognitive ability.

Abstract: The results of a laboratory study of 276 individuals replicate past findings for cooperative behavior as a form of contextual performance and extend past research by providing evidence that voice (constructive change-oriented communication) may be another form of contextual performance. Conscientiousness, extraversion, and agreeableness related more strongly to voice behavior and cooperative behavior than to task performance. Cognitive ability related more strongly to task performance than to voice behavior or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

29
739
5
19

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 867 publications
(792 citation statements)
references
References 48 publications
29
739
5
19
Order By: Relevance
“…When employees work in teams, those who are dispositionally cooperative will be aware of opportunities to help others and they will target citizenship behaviors at their coworkers. In support of this, Hough (1992) and Borman and Motowidlo (1993) demonstrated significant relationships between agreeableness and teamwork, while Johnson (2001) and LePine and Van Dyne (2001) demonstrated positive relationships between agreeableness and cooperative behavior directed at other group members (see also Hurtz & Donovan, 2000;Van Scotter & Motowidlo, 1996). Thus, H2b: Agreeableness will be positively related to helping coworkers.…”
Section: Personality Task Performance and Helpingmentioning
confidence: 91%
See 3 more Smart Citations
“…When employees work in teams, those who are dispositionally cooperative will be aware of opportunities to help others and they will target citizenship behaviors at their coworkers. In support of this, Hough (1992) and Borman and Motowidlo (1993) demonstrated significant relationships between agreeableness and teamwork, while Johnson (2001) and LePine and Van Dyne (2001) demonstrated positive relationships between agreeableness and cooperative behavior directed at other group members (see also Hurtz & Donovan, 2000;Van Scotter & Motowidlo, 1996). Thus, H2b: Agreeableness will be positively related to helping coworkers.…”
Section: Personality Task Performance and Helpingmentioning
confidence: 91%
“…Consistent with this, Borman, White, and Dorsey (1995) reported that likeability had little effect on task performance; LePine and Van Dyne (2001) showed no relationship between agreeableness and task performance on a laboratory task where performance was operationalized as decision making accuracy; and at least three meta-analyses have failed to show a consistent relationship between agreeableness and task performance (Hough et al, 1990;Hurtz & Donovan, 2002;Salgado, 1997). Commenting on these findings, Johnson (2003) noted that agreeableness may predict task performance in some jobs but not in others.…”
Section: Personality Task Performance and Helpingmentioning
confidence: 97%
See 2 more Smart Citations
“…A smaller body of research has investigated the importance of other predictors such as leadership (Hofmann et al, 2003;Smith, Organ, & Near, 1983) and various personality characteristics (Bateman & Crant, 1993;LePine & Van Dyne, 2001). Yet there are other potentially important factors that have received little attention.…”
mentioning
confidence: 99%